Decreased Mitochondrial Function Among Healthy Infants Exposed to Antiretrovirals During Gestation, Delivery and the Neonatal Period. Issue 12 (December 2015) - Noguera-Julian, Antoni; Morén, Constanza; Rovira, Núria; Garrabou, Glòria; Catalán, Marc; Sánchez, Emília; Cardellach, Francesc; Miró, Óscar; Fortuny, Clàudia
Abstract : Background: Antiretroviral (ARV)-associated mitochondrial toxicity in HIV/ARV-exposed healthy infants is a concern. Clinically relevant toxicity is rare. Hyperlactatemia is common but nonspecific, both increased and decreased mitochondrial DNA (mtDNA) level has been reported. Mitochondrial function has scarcely been investigated. Methods: In a prospective observational study of 133 HIV/ARV-exposed infants, mtDNA content was measured with quantitative real-time polymerase chain reaction, and mitochondrial respiratory chain enzymatic activity of complex IV (CIV) and mitochondrial mass (MM) were assessed spectrophotometrically from cryopreserved peripheral blood mononuclear cells obtained at 6 weeks and 3, 6 and 12 months of age and compared with a control group. Results: Most mothers (88%) received combined ARV therapy during pregnancy, and 92% of infants received zidovudine monotherapy. No infant had clinical evidence of mitochondrial disease during follow-up. Nonsignificant higher MM and lower mtDNA levels (normalized by MM) were observed over time in HIV/ARV-exposed infants. MM-normalized CIV activity was consistently lower in HIV/ARV-exposed children than in controls over time (0.09 vs. 0.35, 0.12 vs. 0.38, 0.13 vs. 0.24 and 0.14 vs. 0.24 nmol/min/mg at 6 weeks and 3, 6 and 12 months; P = 0.014, P < 0.0001, P = 0.065 and P = 0.011, respectively) and showed a linear trend toward normalization with age ( P < 0.01). In HIV/ARV-exposed infants, an inverse correlation between CIV activity and mtDNA levels was observed until 6 months of age (r = −0.327, P = 0.016; r = −0.311, P = 0.040 and r = −0.275, P = 0.046). Conclusions: Mitochondrial-encoded CIV activity was consistently lower among HIV/ARV-exposed healthy infants and inversely correlated with mtDNA levels, suggesting upregulation of the latter. Abstract : Supplemental Digital Content is available in the text.